Ion beam bioeng ineering research in Thailand - Anuntalabhochai S. (2017)
This review summarizes recent progress of a newly developed novel bioengineering technology, namely low-energy ion beam bioengineering (IBB), achieved at Chiang Mai University, Thailand. Low-energy IBB has demonstrated powerful impacts and highly potential applications on biology, agriculture, horticulture and life science owing to multiple-factor interaction between energetic ions and biological organisms as well as low-cost and convenience in operation. Since late 1990s, IBB research programs have been vigorously carried out at Chiang Mai University. A group of scientists consisting of physicists, biologists, horticulturists, agriculturists, chemists, and medical scientists have developed special IBB ion beam lines and relevant techniques to use low-energy ion beam bombardment of biological organisms to induce mutation breeding and gene transfer. Besides the IBB applications, research interests are also focused onto basic mechanisms on ion interaction with DNA and biological cells to reveal physics and biology involved in the ion beam inductions of mutation and gene transfer. The results have been applied to serve developments of local agriculture and horticulture and promote national scientific research qualities. The contents include introductions to lowenergy IBB techniques and facilities, and chapters on ion beam induced gene transfer, ion interaction with the cell envelope, ion beam induced mutation, and ion interaction with living cells and DNA. © 2010 by Nova Science Publishers, Inc. All rights reserved.